Emotional state and its impact on sleep quality in middle-aged and elderly people - Alijošiūtė, Eliana; Mikaliūkštienė, Aldona (Slauga. Mokslas ir praktika, 2023)
Sleep quality is a key determinant of good health, and its importance cannot be overlooked among middle-aged and elderly people, given that sleep disturbances and difficulty falling asleep become more common with age, which affects the emotional well-being and quality of life of middle-aged and elderly people. Evidence shows that while the need for sleep remains the same throughout a person’s life, the ability to get enough sleep decreases with age. The aim of this paper is to review and present recent literature on the emotional state of middle-aged and elderly people and its impact on sleep quality. Methods – systematic literature review of PubMed and Google Scholar databases on the emotional state of middle-aged and elderly people and its impact on sleep quality. Results and conclusions. 9 articles were included in the systematic review. The studies show that worsening emotional state, symptoms of depression, anxiety and grief lead to poorer sleep quality and, conversely, that poor sleep quality can contribute to the development of these emotional conditions.